Hydrogen bubble nucleation in α-iron. (June 2017) - Geng, W.T.; Wan, Liang; Du, Jun-Ping; Ishii, Akio; Ishikawa, Nobuyuki; Kimizuka, Hajime; Ogata, Shigenobu
Abstract: We report a first-principles study on how H2 molecules emerge in a nanovoid in α-iron. In a 9-vacancy void, after the walls are decorated with 24 H atoms, only H-dimers are allowed to be adsorbed on the walls; whereas in a spherical 27-vacancy void, H2 molecules start to appear in the center of the void after the walls are saturated by 54 H atoms. The bubble pressure can reach 3.5 GPa, comparable to the measured H2 pressure in blisters at the micrometer scale. The H-saturated nanovoid attracts vacancy more strongly than does the pristine nanovoid through strong H-vacancy interaction. Graphical abstract: